<h2><u><em>
If you rather have the link to get this info lmk!!</em></u></h2>
Example: f(x) = 2x+3 and g(x) = x2
"x" is just a placeholder. To avoid confusion let's just call it "input":
f(input) = 2(input)+3
g(input) = (input)2
Let's start:
(g º f)(x) = g(f(x))
First we apply f, then apply g to that result:
Function Composition
- (g º f)(x) = (2x+3)2
What if we reverse the order of f and g?
(f º g)(x) = f(g(x))
First we apply g, then apply f to that result:
Function Composition
- (f º g)(x) = 2x2+3
We get a different result! When we reverse the order the result is rarely the same. So be careful which function comes first.
<h2 />
Answer:
the solution is x = 2 and y = 4 OR (2,4)
Step-by-step explanation:
From the question
Equation 1: 3x-2y= -2
Equation 2: 3x + y = 10
Subtract equation 1 from equation 2, that is
3x + y = 10 - (3x -2y = -2)
You get
3x - 3x + y - (-2y) = 10 - (-2)
0 + y + 2y = 10 + 2
3y = 12
Divide both sides by 3
∴ y = 12/3
y = 4
Substitute the value of y into equation 2 to get x
3x + y = 10
3x + 4 = 10
Then,
3x = 10 - 4
3x = 6
Divide both sides by 3
∴ x = 6/3
x = 2
Hence, the solution is x = 2 and y = 4
8th grade = 3x = 3(47) = 141 band members.
7th + 8th = 188
7th = x
8th = 3x
x + 3x = 188 ; x = 47 ; 47 + 3(47) = 47 + 141 = 188
4x = 188
4x / 4 = 188 / 4
x = 47 --> 7th grade
8th grade = 3x = 3(47) = 141
To check:
x + 3x = 188 ; x = 47 ;
47 + 3(47) = 188
47 + 141 = 188
188 = 188
Answer:
Step-by-step explanation:
f(x) = -8x + 20
f(-1) = -8* -1 + 20 = 8+20 =28
5 - 2[f(-1)] = 5 - 2*28 = 5 - 56 = -51